A new species and new records of Gripopterygidae (Plecoptera) from the Serra dos Orgãos, Rio de Janeiro State, Brazil - Avelino-Capistrano, Fernanda; Nessimian, Jorge Luiz (Zootaxa, 2013)
A new species of the stonefly family Gripopterygidae, Tupiperla barbosai sp. nov. is described from the Serra dos Órgãos, Rio de Janeiro State, Brazil. Additionally, two new species records are presented from the Serra dos Órgãos, Tupiperla reichardti Froehlich and Guaranyperla guapiara Froehlich, the latter a new record for Rio de Janeiro State. A review of the species of Gripopterygidae from these mountains is presented including distributional data and taxonomic remarks.